A commercial, benefit driven and secure framework for elearning in cloud computing. Issue 4 (16th January 2015) - Sandhu, Rajinder; Sood, Sandeep K.
ABSTRACT Today's industry demands well‐equipped engineers with practical as well as theoretical knowledge. Providing specialization courses is need of an hour but decline in teacher to student ratio in universities and educational institutions is big hurdle in this vision. Elearning is an ideal solution to this engineering education problem. Traditional elearning platforms are less efficient and prone to sudden failures. In this paper, a cloud‐based commercial and benefit driven elearning system is proposed which has multiple education service providers and separate end user's needs. Proposed system designing and initial assessment is done using Design Science Research (DSR) approach. DSR studies already available knowledge base and formulate requirements of a commercial elearning system. Proposed framework has layered structure consisting of five layers where each layer is dedicated for a specific task. User layer handles all user interactions, management layer manages cloud resources by accurate prediction and cost calculation, security layer provides secure access to data stored on archive layer, archive layer is responsible for proper indexing and storage of data, finally resource layer manages underline hardware of cloud system. Proposed framework is tested against MyGuru2, results indicates that proposed framework is cost effective and provides better QoS requirements. © 2015 Wiley Periodicals, Inc. Comput Appl Eng Educ 23:499–513, 2015; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21621